Single-port laparoscopic hysterectomy: preliminary results - Tormena,Renata Assef (2015)
Summary Objective: to describe the initial results of a laparoscopic single port access hysterectomy and also to evaluate the feasibility and safety of this access. Methods: a prospective study was performed at a tertiary university medical center (Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo) between March 2013 and June 2014. A total of 20 women, referred for hysterectomy due to benign uterine disease, were included in the study after they had signed an informed consent. Outcome measures, including operating time, blood loss, rate of complications, febrile morbidity, visual analogical pain score and length of hospital stay were registered. Results: mean patient age and body mass index (BMI) were 47.8 years and 27.15 kg/m2, respectively. Mean operating time was 165.5 min. Blood loss was minimal, with no blood transfusion. All procedures but one were successfully performed via a single incision and no post-operative complications occurred. We experienced one conversion to multiport laparoscopic hysterectomy due to extensive pelvic adhesions. There was no conversion to “open” total abdominal hysterectomy. None of the patients required narcotics or NSAD post-operatively. Conclusion: single-port hysterectomy is a feasible and safe technique, with no major complications.